A hospital based case control study of female breast cancer risk factors in a Sub-Saharan African country - Gueye, Mamour; Kane Gueye, Serigne Modou; Ndiaye Gueye, Mame Diarra; Diallo, Moussa; Gassama, Oumar; Biaye, Babacar; Lemine, Ahmed Ould; Niasse, Aminata; Mbodji, Aissatou; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Breast cancer is the most common cancer diagnosed in women worldwide with over 1.3 million new cases per year. There is a wide variation in the geographical burden of the disease with the highest incidences seen in the developed regions of the world and the lowest incidences observed in the least developed regions. The objective of this study was to understand further the risks for breast cancer in Senegalese population which can then inform public health strategies to try and reduce the burden of breast cancer. Methods: This matched case control study was conducted in 2015 in Aristide Le Dantec Teaching Hospital in Dakar. All women with pathologically confirmed primary breast cancer were considered as cases. For each case, 2 age-matched women were recruited. We collected and compared demographic factors, family history of breast cancer, socioeconomic variables, reproductive variables (age at menarche, age at first pregnancy and first live birth, parity, menopausal status, duration of breastfeeding), and exogenous hormone use up to 6 months. Odds ratios from univariate logistic regression were used to estimate the relative risk of breast cancer associated with the various factors, and their predictive effects. Results: In all, 212 women with breast cancer who were diagnosed as having breast cancer and 424 control women were involved in the study. The mean±SD age of cases and controls was 43.37±11.94 years (range 18-83 years) and 42.04±11.08 years (range 18-84 years), respectively. There were no significant differences between cases and controls with regards to marital status, parity, age at menarche, past oral contraceptive use, age at first last full-term pregnancy and history of breastfeeding. Breast cancer risk was significantly greater in women with a family history of the disease (OR 2.12, 95% confidence interval [CI] 1.35-3.31). A significant increase in breast cancer was observed among illiterate women compared to educated women (OR 1.27, CI 1.02-1.58), in premenopausal women and those without occupation. Conclusions: In this study, reproductive factors as early menarche or menopausal status were not associative to the risk of breast cancer and the early age at diagnosis and the positive history of breast cancer suggest a genetic pattern of this disease in Senegalese woman. But this fact is difficult to confirm for financial reasons.